Viral Hepatitis Elimination Strategies and Impact of COVID-19 - Aniqa Abdul Rasool; Mah I Kan Changez (ziauddin University, 2024)
Several public-private partnerships and government-funded programs have concerted years-long efforts toward eliminating viral hepatitis and devised strategies to reach the sustainable development goal (SDG) target by 2030. The recent pandemic has derailed all progress and caused the unfortunate healthcare milestone regression in all elimination programs. Due to fear of contraction of COVID-19, the tested positive patient population and the population at risk jettisoned their outpatient clinic visits and screenings, accruing an unprecedented excess of this ailment for years to follow. The pandemic also unveiled deficiencies in our healthcare's accessibility and distribution, as noticed with the vaccine shortages, increased number of home births, and missing opportunities for antenatal screening and childhood vaccination. All in all, this leaves us with multitudes of questions about our unpreparedness for the current and future pandemics and the urgent need for large-scale efforts to mitigate the gaps if we are to attain the SDG target by 2030.